Hubungan antara religiositas dengan agresivitas pada komunitas pemuda gereja - Wijaya, Eirena Fiola; Goei, Yonathan Aditya; Matahari, David (Konsorsium Psikologi Ilmiah Nusantara, 2018)
A lot of individuals have lived their lives with a strong attachment towards religion; however some of them still have a high aggressive behavior. This phenomenon is also evident in the youth communities within the church. The core teaching of the Christianity is love, in which love is supposed to inhibit individuals to initiate aggressive behavior. This study aims to explore the correlation between religiosity, which has two components (intrinsic religiosity orientation and extrinsic religiosity orientation), towards aggressive behavior in youth communities within the church. This study used quantitative method. To obtain and collect the data, we used the aid of questionnaire distributed through purposive technique towards 87 subjects. The instruments included the Verbal Aggressive Scale for the aggressive behavior, the I/E-R Scales to measure religious orientation, and Faith Development Scale to measure the development of faith in each individual. The result of this research pointed out that there is no significant correlation between intrinsic religious orientation and aggressive behavior and that is a positive correlation between extrinsic religious orientation and aggressive behavior.